Civil mechanism preventing and resolving a conflict of interest in the russian private law (2021)
The article studies the legal mechanism preventing and resolving a conflict of interest in civil law. The Russian public law pays much attention to the prevention of competitive interests but there are still no studies on a conflict of interest in private law. The authors have written this article to consider the relevant legal studies and draw their conclusions. Methods: The authors used the methods of comparative and systemic analysis, synthesis and scientific research to examine such a legal concept as a "conflict of interest in private law". The study aims at analyzing the category of competitive interests in relation to private law, determining its prerequisites, reasons and possible solutions. The authors have concluded that a conflict of interest often causes corporate conflicts among parties involved in corporate relations. Moreover, this type of conflicts arises due to the realization of individual property interests and the possibility of one person to influence the other, for example, a conflict between majority and minority shareholders.